ROTAN JERNANG SEBAGAI PENOPANG KEHIDUPAN MASYARAKAT: KASUS KABUPATEN MUARA ENIM, PROVINSI SUMATERA SELATAN - Sri Lestari (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2017)
Natural dragon’s blood in Muara Enim Regency, South Sumatra Province is decreasing due to forest and land degradation, as well as harvesting activities without considering sustainability aspect. This research aims to determine  management, contribution and factors affecting natural dragon’s blood collection. Primary and secondary data collection was conducted by using household surveys, focus group discussions and field observations. Obtained data were analyzed descriptively, both in qualitative and quantitative methods. The results showed that the community collected dragon’s blood to meet their needs when there was no other source of income, since the dragon’s blood was decreasing significantly, so that the collectors should  entering deeper forest and stay there. Therefore, the collectors will be grouped as many as 4-6 people. There were two ways to collect  dragon’s blood: by bringing the stemmed fruit or by bringing the processed dragon’s blood (resin), depending on the distance of the collection location. Income received by the community from dragon’s blood collection amounted to Rp551,087, which was 20.20% of the total income. Working, income, market and the duration of dragon’s blood collection became a significant factor related to the interest of community to collect dragon’s blood.